2016
DOI: 10.3847/0004-637x/832/1/94
|View full text |Cite
|
Sign up to set email alerts
|

Babcock–leighton Solar Dynamo: The Role of Downward Pumping and the Equatorward Propagation of Activity

Abstract: The key elements of the Babcock-Leighton dynamos are the generation of poloidal field through decay and dispersal of tilted bipolar active regions and the generation of toroidal field through the observed differential rotation. These models are traditionally known as flux transport dynamo models as the equatorward propagations of the butterfly wings in these models are produced due to an equatorward flow at the bottom of the convection zone. Here we investigate the role of downward magnetic pumping near the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 48 publications
(73 reference statements)
1
60
0
1
Order By: Relevance
“…The cycle period then becomes unrealistically short; see Run B2 in Table 1. Karak & Cameron (2016) have shown that a downward pumping near the surface reduces the diffusion of the flux across the surface and helps to achieve a dynamo at a higher value of η t than hitherto. However, even with a reasonable amount of surface pumping, we tend to get decaying solutions unless we increase the observed flux distribution by a small value; see Runs B3-B4.…”
Section: Steady Dynamo Solutionmentioning
confidence: 99%
See 4 more Smart Citations
“…The cycle period then becomes unrealistically short; see Run B2 in Table 1. Karak & Cameron (2016) have shown that a downward pumping near the surface reduces the diffusion of the flux across the surface and helps to achieve a dynamo at a higher value of η t than hitherto. However, even with a reasonable amount of surface pumping, we tend to get decaying solutions unless we increase the observed flux distribution by a small value; see Runs B3-B4.…”
Section: Steady Dynamo Solutionmentioning
confidence: 99%
“…As discussed in Karak & Cameron (2016), the pumping is efficient near the surface (mainly caused by the topological asymmetry of the convective flow), while the deeper convection is weaker and less stratified (Spruit 1997). The pumping helps to boost the efficiency of the dynamo by suppressing the diffusion of toroidal flux through the surface.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations